Exploring the metabolic potential of novel marine Actinobacteria - Inetianbor, Jonathan (2022)
Actinobacteria are filamentous and ubiquitous Gram-positive bacteria with diverse potential to produce significant secondary metabolites, that have end biotechnology applications in medicine, agriculture, environmental and energy sectors. Over the years, the isolation of actinobacteria from terrestrial habitats has resulted in the isolation of the same genera thus decreasing the chances of discovering potential novel metabolites. This research study was aimed at isolating novel actinobacteria from marine habitats and exploring their metabolic potential. The marine environment was the focus of this study because it is still underexplored for the isolation of actinobacteria. A culture-dependent approach with selective media was used to isolate marine actinobacteria. Genotypic methods such as 16S rRNA sequencing, next-generation genomic sequencing by Illumina technology and phenotypic methods were used to characterize the isolates belonging to different genera. Our results showed a total number of nine novel actinobacterial species across six genera (Brachybacterium, Kocuria, Micrococcus, Micromonospora, Streptomyces and Salinibacterium) were isolated including those from previous work done in our laboratory. The small number of actinobacteria isolated could be due to the small aliquots of sample used in the inoculation which might not have captured the true diversity coupled with the fact that actinobacteria represent a small fraction of bacteria in the marine environment. The 16S rRNA gene sequences of the isolates were deposited in the NCBI GenBank database with a unique accession number assigned. ISP-ASW selective media supported the isolation of the most marine actinobacteria. The analysis of the genome sequencing data revealed that the draft genome features of the isolates consisted of assembled genome size which ranged from 3,994,542 bp for NB 16 to 9,849,154 bp for NB 20, and the percentage of G+C content ranged from 62.1% for NB 20 to 72.8% for NB 21 and the total number of gene ranged from 2,416 for NB 19 to 9,567 for NB 18. The analysis of the genomic sequencing data has given an insight into the different classes of BGCs present in the genome of the isolates and a clue to the kind of secondary metabolites that could be screened for from the isolates. A total of 26 biosynthetic gene clusters (BGCs) were detected in the genome of the isolates as predicted by antiSMASH (Antibiotics and Secondary Metabolite Analysis Shell). The ability of the isolates to produce biosurfactants and extracellular enzymes were screened by phenotypic assays on multi-well agar plates. Our results showed that isolates NB 14, NB 16, NB 19, and NB 20 could produce biosurfactants according to phenotypic assay, TLC (thin layer chromatography) and HPLC-MS (high-performance liquid chromatography-mass spectrometer) analyses. Our phenotypic assay for the ability of the isolates to produce extracellular enzymes revealed that isolates NB 2, NB 15 and NB 16 could produce amylase while isolates NB 2, NB 14, NB 15, NB 16, NB 18 NB 19, NB 20, and FOP 8 produce protease and cellulase enzymes and isolate NB 2 could produce lipase. Genomic sequencing analysis also revealed the presence of cellulase and cellulose-related genes in NB 2, NB 18, and FOP 8. Rare marine actinobacteria have found wide applications in many sectors and this has necessitated their search and isolation in recent years. The phenotypic assay to produce extracellular enzymes is not enough to conclude that these isolates could produce these enzymes. The result needs to be backed up with molecular studies. This study has therefore revealed the different diversity of actinobacteria in the marine environment. This marine environment could be a rich reservoir for the isolation of marine actinobacteria and biosynthesis of important compounds and secondary metabolites